Differences in Word and Phoneme Recognition in Quiet, Sentence Recognition in Noise, and Subjective Outcomes between Manufacturer First-Fit and Hearing Aids Programmed to NAL-NL2 Using Real-Ear Measures. - Valente, Michael; Oeding, Kristi; Brockmeyer, Alison; Smith, Steven; Kallogjeri, Dorina (Journal of the American Academy of Audiology, 2018)
Background: The American Speech-Language-Hearing Association (ASHA) and American Academy of Audiology (AAA) have created Best Practice Guidelines for fitting hearing aids to adult patients. These guidelines recommend using real-ear measures (REM) to verify that measured output/gain of hearing aid(s) match a validated prescriptive target. Unfortunately, approximately 70-80% of audiologists do not routinely use REM when fitting hearing aids, instead relying on a manufacturer default "first-fit" setting. This is problematic because numerous studies report significant differences in REM between manufacturer first-fit and the same hearing aids using a REM or programmed-fit. These studies reported decreased prescribed gain/output in the higher frequencies for the first-fit compared with the programmed fit, which are important for recognizing speech. Currently, there is little research in peer-reviewed journals reporting if differences between hearing aids fitted using a manufacturer first-fit versus a programmed-fit result in significant differences in speech recognition in quiet, noise, and subjective outcomes. Purpose: To examine if significant differences were present in monosyllabic word and phoneme recognition (consonant-nucleus-consonant; CNC) in quiet, sentence recognition in noise (Hearing in Noise Test; HINT), and subjective outcomes using the Abbreviated Profile of Hearing Aid Benefit (APHAB) and the Speech, Spatial and Qualities of Hearing (SSQ) questionnaires between hearing aids fit using one manufacturer's first-fit and the same hearing aids with a programmed-fit using REM to National Acoustic Laboratories Nonlinear Version 2 (NAL-NL2) prescriptive target. Research Design: A double-blind randomized crossover design was used. Throughout the study, one investigator performed all REM whereas a second investigator measured speech recognition in quiet, noise, and scored subjective outcome measures. Study Sample: Twenty-four adults with bilateral normal sloping to moderately severe sensorineural hearing loss with no prior experience with amplification. Data Collection and Analysis: The hearing aids were fit using the proprietary manufacturer default first-fit and a programmed-fit to NAL-NL2 using real-ear insertion gain measures. The order of the two fittings was randomly assigned and counterbalanced. Participants acclimatized to each setting for four weeks and returned for assessment of performance via the revised CNC word lists, HINT, APHAB, and SSQ for the respective fitting. Results: (1) A significant median advantage of 15% (p < 0.001; 95% CI: 9.7-24.3%) for words and 7.7% (p < 0.001; 95% CI: 5.9-10.9%) for phonemes for the programmed-fit compared with first-fit at 50 dB sound pressure level (SPL) and 4% (p < 0.01; 95% CI: 1.7-6.3%) for words at 65 dB SPL; (2) No significant differences for the HINT reception threshold for sentences (RTS); (3) A significant median advantage of 4.2% [p < 0.04; 95% confidence interval (CI): -0.6-13.2%] for the programmed-fit compared with the first-fit for the background noise subscale problem score for the APHAB; (4) No significant differences on the SSQ. Conclusions: Improved word and phoneme recognition for soft and words for average speech in quiet were reported for the programmed-fit. Seventy-nine percent of the participants preferred the programmed-fitting versus first-fit. Hearing aids, therefore, should be verified and programmed using REM to a prescriptive target versus no verification using a first-fit.